Part I – January 1968 - Papers - Heteroepitaxial Growth of Molybdenum Thin Films on Insulating Substrates - H. M. Manasevit; F. L. Morritz; D. H. Forbes (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
Single-crystal thin films of molybdenum have been grown. by the pyrolytic decomposition of molybdenum hexafluoride in a hydrogen ambient on various insulating substrates at temperatures front 650° to 900° C. Single-crystal discs of various orientations of magnesium aluminate spinel, a aluminum oxide, magnesium oxide, and the natural facets of beryllium oxide were all observed to exert epitaxial control on the depositing film. Determinations of the crystallographic relationships existing between film and substrates have been made, using X-ray diffraction three-circle goniometry and Laue back-reflection techniques. Using these data, crystallographic overlays have been constructed which suggest a possible interfacial geometry on the basis of a match between metal deposit atoms and metal ion sites in the substrate. A continuing program has been in effect in the Auto-netics Laboratories over the past several years aimed at the development of electronic materials in new and useful forms using chemical vapor deposition techniques. During the course of these investigations, the epitaxy of silicon1"5 and tungstenep7 on single-crystal metal oxide insulators was studied extensively. The deposition of molybdenum is a logical extension of the tungsten work since the crystal structure is identical and the lattice dimensions differ by less than 1 pct. The pyrolytic decomposition of molybdenum hexafluoride in hydrogen was used to grow molybdenum films on the oxide substrates AlzOs, MgA1~04, MgO, and Be0 at from 650" to 900°C, depending on the substrate material. Under the experimental conditions to be described, monocrystalline films of controlled orientation were obtained. The materials investigated and their crystal structure are listed in Table I. EXPERIMENTAL The molybdenum depositions were effected by the hydrogen reduction of molybdenum hexafluoride (MoFe) in a flowing system of hydrogen at atmospheric pressure. The schematic of the apparatus is shown in Fig. 1. The hydrogen, purified by passage through a heated palladium thimble, was mixed with the vapor of the liquid MoFe maintained in a steel bottle at room temperature (25°C). The mixture was passed over the substrate, which was heated by rf induction of a sup-